RESULTS OF ORTHOSES USED ON AMBULATORY PATIENTS WITH BILATERAL CEREBRAL PALSY - ALESSANDRO GIURIZATTO MELANDA; ANA CAROLINA PAULETO; DIELISE DEBONA IUCKSCH; RODRIGO FAUCZ MUNHOZ DA CUNHA; SUHAILA MAHMOUD SMAILI (Acta Ortopédica Brasileira, 2020)
ABSTRACT Objective: To investigate the impact of ankle-foot orthoses (AFO) on subjects diagnosed with bilateral cerebral palsy (CP) using the gait index and temporal data parameters. Methods: Twenty-four subjects, 14 male and 10 female, with a mean age of 11 (5-17 years old), underwent a comprehensive gait analysis under both barefoot (BF) and braced walking conditions. All children had been wearing the orthoses for at least 2 months before the gait analysis. Results: The overall values for the left and right Gait Profile Scores (GPS) did not show statistically significant variations when comparing the same individuals with and without orthoses. Gait velocity increased by 19.5% (p < 0.001), while the cadence decreased by 4% with use of orthosis, although it was not statistically significant (p > 0.05). The stride and the step lengths on both the right and left sides, however, resulted in statistically significant increases, when wearing AFO. Conclusion: AFO, prescribed for assistance by professionals without using gait data, did not significantly affect the gait index (GPS), but improved temporal data. The determination of quantitative clinical parameters for the prescription of orthotics in patients with bilateral CP, as well as orthotics that meet the specific requirements are points to be addressed in the future to obtain more significant effects. Level of evidence III, Case control study.